Existence of a ground state solution for a class of singular elliptic equation without the A–R condition. (February 2018) - Liu, Yanjun; Qi, Shijie; Zhao, Peihao
Abstract: In this paper, we prove the existence of a ground state solution for a class of elliptic problem on R N with the nonlinearity containing both singular and exponential subcritical terms, we get some results without the A–R condition.